2009
DOI: 10.1097/pas.0b013e3181872d3f
|View full text |Cite
|
Sign up to set email alerts
|

Tubulocystic Carcinoma of the Kidney

Abstract: A distinctive tumor described under the terms Bellini duct carcinoma and low-grade collecting duct carcinoma has been referred to by us and others as tubulocystic carcinoma. This renal cell carcinoma subtype is not recognized in the World Health Organization 2004 classification. Herein, we present a detailed study of 31 cases to further characterize this rare subtype of renal cell carcinoma. The tumor occurred in adults (mean age, 54 years) with a strong male predominance (7:1). Grossly, the tumors ranged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(81 citation statements)
references
References 26 publications
1
72
0
8
Order By: Relevance
“…1 TC-RCC is a tumour of adulthood, with a mean age of 60 years and a strong male preponderance. [1][2][3] Patients are often asymptomatic, which has been attributed to the small size of these tumours (usually <2 cm). Patients harbouring larger tumours may, however, present with abdominal pain, distension, or even hematuria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 TC-RCC is a tumour of adulthood, with a mean age of 60 years and a strong male preponderance. [1][2][3] Patients are often asymptomatic, which has been attributed to the small size of these tumours (usually <2 cm). Patients harbouring larger tumours may, however, present with abdominal pain, distension, or even hematuria.…”
Section: Discussionmentioning
confidence: 99%
“…5 Solid areas, small foci of clear cell change or papillary configuration are rare, and may herald aggressive behaviour and worsen clinical outcome. 2,6,7 However, more recent data have suggested that TC-RCCs with focal dedifferentiation (TC-D-RCC) may actually represent hereditary leiomyomatosis RCC syndrome -associated RCC (HLRCC), as some TC-D-RCC cases show loss of fumarate hydratase immunoexpression and S-(2-Succino)-Cysteine (2SC) immunopositivity, similar to HLRCC (Table 1). 8 The histogenesis of TC-RCC remains unclear.…”
Section: Kakkar Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Mostly, such tumors are composed of tubules and cysts lined by a single layer of typical hobnail cells with large nuclei and prominent nucleoli. The literature describing biological behavior, immunohistochemical profiles, ultrastructural features and possible differential diagnostic features of TRCC is limited [2][3][4][5][6]. The oncogenesis of this neoplasm is unclear.…”
Section: Tubulocystic Renal Cell Carcinoma (Trcc) Represents Anmentioning
confidence: 99%